In search of an "international" translation studies: Tracing terceme and tercüme in the blogosphere. Issue 1 (2nd January 2017) - Susam-Saraeva, Şebnem
ABSTRACT: The idea of a more "international" and "multilingual" translation studies has been explored since the beginning of the twenty-first century. It has been argued that a truly international and "de-Westernized" translation studies can and should learn from indigenous and varied conceptualizations of "translation" around the world. The departure point of this article is the idea that before "exporting" concepts out of a given translational tradition for the use of international researchers, one might wish to explore whether these concepts have relevance to present-day practices within the continuation of the same tradition. The objective of the article is to find out whether the Ottoman concepts of terceme and its later derivative tercüme might yield insights into translation as part of digital text production on the internet. Focusing on a successful Turkish mommy blog, the article will seek not to decontextualize terceme or tercüme, but to find out whether at least some of their characteristics can be traced within contemporary blogs in Turkish, and whether they might therefore have insights to offer for researchers working on translation and cyberactivism in general, and translation in the blogosphere in particular.